Torque-Ripple Reduction and Fast Torque Response Strategy for Predictive Torque Control of Induction Motors - Cho, Yongsoo; Bak, Yeongsu; Lee, Kyo Beum (IEEE Transactions on Power Electronics, 2018)
This paper proposes a simple control method of induction motors (IMs) with improved dynamic response and steady-state performance by using a model-based predictive control algorithm. The predictive torque control (PTC) method analyzes the relationship between the electrical torque and stator voltage of IMs by using the stator voltage vector magnitude to obtain the reference voltage vector angle and accurately control the electrical torque. However, the conventional PTC method has a fixed reference voltage vector magnitude and thus has a large torque ripple in the steady state and slow dynamics in the transient state. The proposed PTC method is based on mathematical equations, which allow minimization of torque error and calculation of a relevant reference voltage to establish a better dynamic response in the transient state and accurate control performance in the steady state. Excellent steady-state performance and a quick dynamic response of the proposed method are proved by the simulation and experimental results.
Keywords: Fast torque response; Mathematical equations; Model based predictive control; Predictive torque controls; Simple control method; Space Vector Modulation; Steady state performance; Torque-ripple reduction; Induction motor (IM) drives; predictive torque control (PTC); space vector modulation; torque ripple reduction